2011
DOI: 10.1203/pdr.0b013e318225fbcb
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Response in Preterm Fetal Sheep Exposed to Systemic Endotoxinaemia

Abstract: Exposure of the fetus to antenatal inflammation can occur from chorioamnionitis, which may progress to a fetal inflammatory response syndrome (FIRS) and to fetal sepsis. We tested whether the fetal myocardium responded to systemic Gram-negative endotoxinaemia. We hypothesized that the myocardium would respond to inflammation by changes in hypoxia-inducible factor-␣ (HIF-1␣), inducible NO-synthase (iNOS), Toll-like receptors 2 and 4 (TLR2 and TLR4), IL-6, and phosphorylated signal transducer and activator of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Cardiac dysfunction is a possible explanation for increases in CBF in the HC group, but our infants were asymptomatic, healthy term newborns without differences in heart rate between control and HC or sexes. 23, 29, 30, 31 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysfunction is a possible explanation for increases in CBF in the HC group, but our infants were asymptomatic, healthy term newborns without differences in heart rate between control and HC or sexes. 23, 29, 30, 31 …”
Section: Discussionmentioning
confidence: 99%
“…Protein content in the supernatant was determined using the Micro BCA Protein Assay Kit (Thermo Fisher Scientific, Rockford, IL), with BSA as the standard. Western blots were performed as previously described (40). The following dilutions for antibodies were used: 1:1,000 for monoclonal anti-β-actin clone AC-1 (Sigma-Aldrich), anti-MLC antibody (Abcam, Cambridge, UK), anti-iNOS (BD Transduction Laboratories, Franklin Lakes, NJ), anti-TAK-1 (Cell Signaling Technology, Danvers, MA), and anti-phospho-p38 MAPK out of the PathScan Multiplex Western Cocktail II (Cell Signaling Technology).…”
Section: Western Blottingmentioning
confidence: 99%
“…Conversely, changes in systolic and diastolic blood pressure and increased resting heart rates have been observed in adult rats after neonatal exposure to hyperoxia (Yzydorczyk et al, 2008). Most recently, Seehase et al (2011)reported that antenatal exposure of fetal sheep to endotoxinaemia resulted in cardiac inflammation and dysfunction within 3 days.…”
Section: Animal Studiesmentioning
confidence: 99%